Binge drinking and perceived ethnic discrimination among Hispanics/Latinos: Results from the Hispanic community health study/study of Latinos sociocultural ancillary study. Issue 3 (2nd July 2016) - Ornelas, India J.; Lapham, Gwen T.; Salgado, Hugo; Williams, Emily C.; Gotman, Nathan; Womack, Veronica; Davis, Sonia; Penedo, Frank; Smoller, Sylvia; Gallo, Linda C.
ABSTRACT: The study assessed whether overall perceived ethnic discrimination and four unique discrimination types were associated with binge drinking in participants from the Hispanic Community Health Study/Study of Latinos who also completed the Hispanic Community Health Study/Study of Latinos Sociocultural Ancillary Study ( n  = 5, 313). In unadjusted analyses that were weighted for sampling strategy and design, each unit increase in discrimination type was associated with a 12–63% increase in odds of binge drinking; however, after adjusting for important demographic variables including age, sex, heritage group, language, and duration of U.S. residence, there was no longer an association between discrimination and binge drinking. Further research still needs to identify the salient factors that contribute to increased risk for binge drinking among Hispanics/Latinos.